A study of the penetration behaviour of mild-steel-cored ammunition against boron carbide ceramic armours - Crouch, Ian G.; Appleby-Thomas, Gareth J.; Hazell, Paul J. (Elsevier, 2015)
In this study, the penetration behaviour of a Mild Steel Cored (MSC) round, 7.62 mm in diameter and 39 mm in length, commonly known as the AK47 round, was studied since it still forms an important part of the threat spectrum for personnel body armour systems. Likewise, boron carbide strike face materials were selected since this armour material is often the material of choice for ultralightweight body armour systems for protection against this particular threat. The presence of two, relatively soft, intermediate materials (the copper jacket and filler material of the bullet, and a fibre-reinforced polymer cladding layer on the ceramic) between the mild steel core and the boron carbide target was examined using reverse ballistics techniques, flash x-radiography and round recovery measurements. This was supported by selective numerical simulations using the computer code ANSYS-AUTODYN. It was found that stripping of the jacket, from the AK47 MSC rounds, makes a difference to its penetrating ability: the mild steel core is significantly reduced in length, and mass, when the jacket is not present. The magnitude of this effect is much greater than previously reported for high-strength steel-cored rounds and for tungsten carbide-cored rounds. The penetration event appears to be a twostage process: mushrooming of the mild steel core on, or near, the surface of the ceramic, followed by a linear erosion process as the core penetrates the ceramic itself. The second step has not been reported previously for MSC rounds.
Keywords: AK47 ammunition; Boron carbide ceramic armour; Reverse ballistics; Numerical simulations